Optical glass, optical element and optical instrument

By rationally designing the composition of optical glass, especially controlling the proportion of components such as SiO2, B2O3, La2O3, Gd2O3, ZrO2, Nb2O5, TiO2, etc., the shortcomings of optical glass in terms of high refractive index and mechanical properties are solved, and the goals of high Young's modulus and hardness are achieved to meet the needs of high-performance optoelectronic products.

CN119504137APending Publication Date: 2025-02-25CDGM OPTICAL GLASS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311066491.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing optical glasses have shortcomings in high refractive index and mechanical properties, and it is difficult to meet the needs of high-performance optoelectronic products, especially in terms of high hardness and durability.

Method used

By rationally designing the composition of optical glass, it contains SiO2, B2O3, La2O3, Gd2O3, ZrO2, Nb2O5, TiO2 and other components, and controls its proportions to achieve the goal of high Young's modulus and hardness.

Benefits of technology

It achieves excellent mechanical properties of optical glass, high Young's modulus and hardness, and meets the needs of high-performance optical instruments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004409593010000141
    Figure BDA0004409593010000141
  • Figure BDA0004409593010000151
    Figure BDA0004409593010000151
  • Figure BDA0004409593010000171
    Figure BDA0004409593010000171
Patent Text Reader

Abstract

The invention provides optical glass, which comprises the following components in percentage by weight: 1 to 10 percent of SiO2; 1 to 10 percent of B2O3; the content of La2O3 is 35%-50%; 6 to 20 percent of Gd2O3; 3 to 13 percent of ZrO2; 3 to 15 percent of Nb2O5; the ratio of the (B2O3 + La2O3) to the (Gd2O3 + Nb2O5 + TiO2) is 0.7 to 2.5, and the ratio of the (B2O3 + La2O3) to the (Gd2O3 + Nb2O5 + TiO2) to Through reasonable component design, the optical glass provided by the invention has high Young modulus and hardness and excellent mechanical properties, and can be used in high-performance optical instruments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to optical glass, in particular to optical glass with excellent mechanical properties, and glass preforms, optical elements and optical instruments made of the optical glass. Background Art

[0002] In recent years, the rapid development of digitalization and high precision of optical instruments has put forward higher requirements for the lightweight and miniaturization of optical elements used in various optical instruments such as digital cameras, video cameras and other photographic equipment, projectors, projection televisions and other projection equipment. Under the same radius of curvature, the higher the refractive index of the glass, the larger the imaging field of view, which is conducive to reducing the number of optical elements in the optical instrument. With the development trend of miniaturization of optical instruments, the demand trend of high refractive index optical glass is becoming more and more obvious. In order to achieve the miniaturization of optical elements, when optical glass is processed into smaller or thinner optical elements, if its Young's modulus is small, it is easy to deform during use. Therefore, the development of high refractive index optical glass with a higher Young's modulus plays an important role in the development of high-performance optoelectronic products. In the prior art, optical glass is widely used in the fields of vehicle-mounted, monitoring and security, but the optical glass used in this field needs to have a higher hardness to resist the wear of sand and stones during vehicle driving and extend the service life of the optical glass. Summary of the invention

[0003] Based on the above reasons, the technical problem to be solved by the present invention is to provide an optical glass with excellent mechanical properties.

[0004] The technical solution adopted by the present invention to solve the technical problem is:

[0005] Optical glass, its components expressed in weight percentage, contains: SiO 2 :1~10%; B 2 O 3 :1~10%; La 2 O 3 :35~50%;Gd 2 O 3 :6~20%;ZrO 2 :3~13%; Nb 2 O 5 :3~15%;TiO 2 :8~22%, among which (B 2 O 3 +La 2 O 3 ) / (Gd 2 O 3 +Nb 2 O 5 +TiO 2 ) is 0.7~2.5.

[0006] Furthermore, the optical glass, expressed in weight percentage, further contains: ZnO: 0-5%; and / or RO: 0-6%; and / or Rn 2 O: 0~5%; and / or WO 3 :0~5%;and / or Ta 2 O 5 : 0-5%; and / or Al 2 O 3 :0~5%;and / or Yb 2 O 3 :0~8%;and / or GeO 2 :0~3%;and / or P 2 O 5 : 0-4%; and / or clarifier: 0-1%, wherein RO is one or more of MgO, CaO, SrO, BaO, Rn 2 O is Li 2 O、Na 2 O.K 2 O, the clarifier is Sb 2 O 3 SnO 2 、CeO 2 One or more of .

[0007] Optical glass, its components are expressed in weight percentage, consisting of SiO 2 :1~10%; B 2 O 3 :1~10%; La 2 O 3 :35~50%;Gd 2 O 3 :6~20%;ZrO 2 :3~13%; Nb 2 O 5 :3~15%;TiO 2 : 8~22%; ZnO: 0~5%; RO: 0~6%; Rn 2 O: 0~5%; WO 3 :0~5%;Ta 2 O 5 :0~5%;Al 2 O 3 :0~5%; Yb 2 O 3 :0~8%;GeO 2 :0~3%;P 2 O 5 :0~4%;Clarifying agent:0~1%, wherein (B 2 O 3 +La2 O 3 ) / (Gd 2 O 3 +Nb 2 O 5 +TiO 2 ) is 0.7-2.5, RO is one or more of MgO, CaO, SrO, BaO, Rn 2 O is Li 2 O、Na 2 O.K 2 O, the clarifier is Sb 2 O 3 SnO 2 、CeO 2 One or more of .

[0008] Furthermore, the optical glass, whose components are expressed in weight percentage, satisfies one or more of the following 12 conditions:

[0009] 1) SiO 2 +B 2 O 3 : 3-18%, preferably SiO 2 +B 2 O 3 : 5-15%, more preferably SiO 2 +B 2 O 3 : 7~13%;

[0010] 2) La 2 O 3 +Y 2 O 3 +Gd 2 O 3 : 45-65%, preferably La 2 O 3 +Y 2 O 3 +Gd 2 O 3 : 50-63%, more preferably La 2 O 3 +Y 2 O 3 +Gd 2 O 3 : 52~60%;

[0011] 3)(La 2 O 3 +Gd 2 O 3 ) / Nb 2 O 53.5 to 15.0, preferably (La 2 O 3 +Gd 2 O 3 ) / Nb 2 O 5 is 4.0 to 10.0, more preferably (La 2 O 3 +Gd 2 O 3 ) / Nb 2 O 5 is 5.0 to 8.0, and more preferably (La 2 O 3 +Gd 2 O 3 ) / Nb 2 O 5 5.5~6.5;

[0012] 4) SiO 2 / B 2 O 3 0.4 to 4.0, preferably SiO 2 / B 2 O 3 0.5 to 3.0, more preferably SiO 2 / B 2 O 3 is 0.6 to 2.0, and SiO is more preferred 2 / B 2 O 3 0.7~1.2;

[0013] 5)(SiO 2 +B 2 O 3 ) / Gd 2 O 3 0.3 to 2.5, preferably (SiO 2 +B 2 O 3 ) / Gd 2 O 3 0.4 to 2.0, more preferably (SiO 2 +B 2 O 3 ) / Gd 2 O 3 is 0.5 to 1.5, more preferably (SiO 2 +B 2 O 3 ) / Gd 2 O 3 0.7~1.2;

[0014] 6)(SiO 2+B 2 O 3 +La 2 O 3 ) / ZrO 2 4.0 to 15.0, preferably (SiO 2 +B 2 O 3 +La 2 O 3 ) / ZrO 2 5.0 to 12.0, more preferably (SiO 2 +B 2 O 3 +La 2 O 3 ) / ZrO 2 6.5 to 10.0, more preferably (SiO 2 +B 2 O 3 +La 2 O 3 ) / ZrO 2 7.5~9.0;

[0015] 7) B 2 O 3 / TiO 2 0.1~1.0, preferably B 2 O 3 / TiO 2 0.2 to 0.8, more preferably B 2 O 3 / TiO 2 is 0.2 to 0.7, and B is more preferred 2 O 3 / TiO 2 0.3~0.5;

[0016] 8)(Gd 2 O 3 +Nb 2 O 5 +TiO 2 ) / (SiO 2 +B 2 O 3 ) is 1.0 to 8.0, preferably (Gd 2 O 3 +Nb 2 O 5 +TiO 2 ) / (SiO 2 +B 2 O 3 ) is 1.5 to 6.0, more preferably (Gd 2 O 3 +Nb2 O 5 +TiO 2 ) / (SiO 2 +B 2 O 3 ) is 2.0 to 5.0, and more preferably (Gd 2 O 3 +Nb 2 O 5 +TiO 2 ) / (SiO 2 +B 2 O 3 ) is 2.5~4.0;

[0017] 9)(Gd 2 O 3 +TiO 2 ) / (La 2 O 3 +Nb 2 O 5 ) is 0.3 to 0.9, preferably (Gd 2 O 3 +TiO 2 ) / (La 2 O 3 +Nb 2 O 5 ) is 0.35 to 0.8, more preferably (Gd 2 O 3 +TiO 2 ) / (La 2 O 3 +Nb 2 O 5 ) is 0.4 to 0.7, and more preferably (Gd 2 O 3 +TiO 2 ) / (La 2 O 3 +Nb 2 O 5 ) is 0.45~0.6;

[0018] 10)(B 2 O 3 +La 2 O 3 ) / (Gd 2 O 3 +Nb 2 O 5 +TiO 2 ) is 0.8 to 2.0, preferably (B 2 O 3 +La 2 O 3 ) / (Gd2 O 3 +Nb 2 O 5 +TiO 2 ) is 0.9 to 1.7, more preferably (B 2 O 3 +La 2 O 3 ) / (Gd 2 O 3 +Nb 2 O 5 +TiO 2 ) is 1.0~1.5;

[0019] 11)(B 2 O 3 +La 2 O 3 ) / (Gd 2 O 3 +SiO 2 ) is 1.5 to 5.5, preferably (B 2 O 3 +La 2 O 3 ) / (Gd 2 O 3 +SiO 2 ) is 2.0 to 4.0, more preferably (B 2 O 3 +La 2 O 3 ) / (Gd 2 O 3 +SiO 2 ) is 2.3 to 3.3, and more preferably (B 2 O 3 +La 2 O 3 ) / (Gd 2 O 3 +SiO 2 ) is 2.5~3.2;

[0020] 12) B 2 O 3 / (ZrO 2 +Y 2 O 3 ) is 0.2 to 2.5, preferably B 2 O 3 / (ZrO 2 +Y 2 O 3 ) is 0.4 to 2.0, more preferably B 2 O 3 / (ZrO 2 +Y2 O 3 ) is 0.5 to 1.5, and B is more preferably 2 O 3 / (ZrO 2 +Y 2 O 3 ) is 0.6~1.0.

[0021] Furthermore, the optical glass, whose components are expressed in weight percentage, satisfies one or more of the following five conditions:

[0022] 1)(ZnO+Y 2 O 3 ) / Gd 2 O 3 is 0.8 or less, preferably (ZnO+Y 2 O 3 ) / Gd 2 O 3 is 0.6 or less, more preferably (ZnO+Y 2 O 3 ) / Gd 2 O 3 is 0.01 to 0.5, and more preferably (ZnO+Y 2 O 3 ) / Gd 2 O 3 0.05~0.3;

[0023] 2) ZnO / (SiO 2 +B 2 O 3 ) is 0.8 or less, preferably ZnO / (SiO 2 +B 2 O 3 ) is 0.6 or less, and more preferably ZnO / (SiO 2 +B 2 O 3 ) is 0.01 to 0.5, and ZnO / (SiO 2 +B 2 O 3 ) is 0.02~0.3;

[0024] 3)RO / Nb 2 O 5 0.8 or less, preferably RO / Nb 2 O 5 0.5 or less, more preferably RO / Nb 2 O 5 is 0.3 or less, and more preferably RO / Nb 2 O 5 is less than 0.1;

[0025] 4)(B 2 O 3 +La 2 O 3 +Y 2 O 3 +RO) / Gd 2 O 3 2.0 to 7.0, preferably (B 2 O 3 +La 2 O 3 +Y 2 O 3 +RO) / Gd 2 O 3 2.5 to 6.0, more preferably (B 2 O 3 +La 2 O 3 +Y 2 O 3 +RO) / Gd 2 O 3 is 3.0 to 4.6, and more preferably (B 2 O 3 +La 2 O 3 +Y 2 O 3 +RO) / Gd 2 O 3 3.5~4.5;

[0026] 5)(RO+GeO 2 +Y 2 O 3 +Ta 2 O 5 ) / La 2 O 3 is 0.3 or less, preferably (RO+GeO 2 +Y 2 O 3 +Ta 2 O 5 ) / La 2 O 3 is 0.2 or less, more preferably (RO+GeO 2 +Y 2 O 3 +Ta 2 O 5 ) / La 2 O 3 is 0.15 or less, and more preferably (RO+GeO 2 +Y 2 O 3 +Ta2 O 5 ) / La 2 O 3 is below 0.1,

[0027] The RO is one or more of MgO, CaO, SrO and BaO.

[0028] Furthermore, the optical glass has components expressed in weight percentage, wherein: SiO 2 : 2-8%, preferably SiO 2 : 3-7%; and / or B 2 O 3 : 2-9%, preferably B 2 O 3 : 4-8%; and / or La 2 O 3 : 37-47%, preferably La 2 O 3 : 41-46%; and / or Y 2 O 3 : 0-4%, preferably Y 2 O 3 :0.1~3%; and / or Gd 2 O 3 : 8-18%, preferably Gd 2 O 3 :11~15%; and / or ZrO 2 : 4-11%, preferably ZrO 2 : 6-10%; and / or Nb 2 O 5 : 5-13%, preferably Nb 2 O 5 : 7-12%; and / or TiO 2 : 10-20%, preferably TiO 2 : 13-18%; and / or ZnO: 0-4%, preferably ZnO: 0.1-3%; and / or RO: 0-4%, preferably RO: 0-2%; and / or Rn 2 O: 0-3%, preferably Rn 2 O: 0~1%; and / or WO 3 : 0-3%, preferably WO 3 :0~1%;and / or Ta 2 O 5 : 0~3%, preferably Ta 2 O 5 :0~1%;and / or Al 2 O 3 : 0-3%, preferably Al 2 O 3 :0~1%;and / or Yb2 O 3 : 0-5%, preferably Yb 2 O 3 :0~1%;and / or GeO 2 : 0-2%, preferably GeO 2 :0~1%;and / or P 2 O 5 : 0-2%, preferably P 2 O 5 : 0-1%; and / or clarifier: 0-0.5%, preferably clarifier: 0-0.2%, wherein RO is one or more of MgO, CaO, SrO, BaO, Rn 2 O is Li 2 O、Na 2 O.K 2 O, the clarifier is Sb 2 O 3 SnO 2 、CeO 2 One or more of .

[0029] Furthermore, the optical glass does not contain WO 3 ; and / or does not contain Ta 2 O 5 ; and / or does not contain RO; and / or does not contain Rn 2 O; and / or does not contain P 2 O 5 ; and / or does not contain Al 2 O 3 ; and / or does not contain GeO 2 ; and / or does not contain Yb 2 O 3 , the RO is one or more of MgO, CaO, SrO, BaO, Rn 2 O is Li 2 O、Na 2 O.K 2 One or more of O.

[0030] Furthermore, the refractive index n of the optical glass is d is 1.98 to 2.15, preferably 1.99 to 2.10, more preferably 2.00 to 2.10, further preferably 2.01 to 2.10, and further preferably 2.03 to 2.07. The Abbe number v d It is 22-31, preferably 23-30, more preferably 24-29, further preferably 25-28.

[0031] Furthermore, the thermal expansion coefficient of the optical glass is -30 / 70℃90×10 -7 / K or less, preferably 80×10 -7 / K or less, more preferably 75×10 -7 / K or less; and / or acid resistance stability D A Two or more types, preferably one type; and / or 70 480nm or less, preferably λ 70 470nm or less, preferably λ 70 is below 465nm; and / or λ 5 390nm or less, preferably λ 5 380nm or less, preferably λ 5 375nm or less; and / or weather resistance CR is 2 or more, preferably 1; and / or Knoop hardness H K 630×10 7 Pa or more, preferably 650×10 7 Pa or more, more preferably 660×10 7 Pa or more; and / or Young's modulus E is 11000×10 7 Pa or more, preferably 12000×10 7 Pa or more, more preferably 13000×10 7 Pa or above; and / or the bubble degree is above grade A, preferably A 0 Grade A or above, preferably A 00 Grade; and / or density ρ is 5.50g / cm 3 Below, preferably 5.40 g / cm 3 Below, more preferably 5.30g / cm 3 Below; and / or wear degree F A It is 90-140, preferably 100-130, more preferably 110-123.

[0032] The glass preform is made of the above optical glass.

[0033] The optical element is made of the above optical glass, or made of the above glass preform.

[0034] An optical instrument contains the above optical glass and / or contains the above optical element.

[0035] The beneficial effects of the present invention are: through reasonable component design, the optical glass of the present invention has a higher Young's modulus and hardness, excellent mechanical properties, and meets the use of high-performance optical instruments. DETAILED DESCRIPTION

[0036] The following will describe the embodiments of the optical glass of the present invention in detail, but the present invention is not limited to the following embodiments, and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, although there are appropriate omissions of descriptions of the repeated descriptions, the gist of the invention will not be limited thereby, and in the following content, the optical glass of the present invention is sometimes referred to as glass.

[0037] [Optical glass]

[0038] The following is an explanation of the range of each component (ingredient) of the optical glass of the present invention. In the present invention, unless otherwise specified, the content and total content of each component are all expressed in weight percentage (wt%), that is, the content and total content of each component are expressed in weight percentage relative to the total amount of glass material converted into oxide composition. Here, the "composition converted into oxide" means that when the oxides, complex salts and hydroxides used as raw materials for the optical glass components of the present invention decompose and transform into oxides during melting, the total amount of the oxide material is taken as 100%.

[0039] Unless otherwise specified in specific circumstances, the numerical ranges listed in the present invention include upper and lower limits, "above" and "below" include endpoint values, and all integers and fractions included in the range, without being limited to the specific values ​​listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.

[0040] <Essential Components and Optional Components>

[0041] SiO 2 The viscosity of molten glass can be increased, the coloring of glass can be reduced, the chemical stability of glass can be improved, and the resistance to devitrification can be improved. In the present invention, by containing more than 1% SiO 2 To obtain the above effects, SiO 2 The content of SiO is 2% or more, preferably SiO 2 The content of SiO is 3% or more. 2 If the content of SiO is too high, the melting difficulty of the glass will increase, the transition temperature will increase, and the refractive index will decrease. 2 The upper limit of the content is 10%, preferably 8%, and more preferably 7%.

[0042] B 2 O 3 It can improve the melting property and devitrification resistance of glass, and is beneficial to lowering the transition temperature of glass. 2 O 3 In order to obtain the above effect, it is preferred to contain 2% or more B 2 O3 , more preferably containing 4% or more B 2 O 3 If B 2 O 3 If the content of B is too high, the chemical stability of the glass will deteriorate and the refractive index will decrease, which is not conducive to obtaining the high refractive index of the present invention. 2 O 3 The content of is 10% or less, preferably 9% or less, and more preferably 8% or less.

[0043] In some embodiments, SiO 2 and B 2 O 3 Total content of SiO 2 +B 2 O 3 Controlling it within the range of 3-18% is beneficial to improving the chemical stability of the glass and optimizing the abrasiveness of the glass. 2 +B 2 O 3 3 to 18%, more preferably SiO 2 +B 2 O 3 5 to 15%, more preferably SiO 2 +B 2 O 3 It is 7 to 13%.

[0044] In some embodiments, SiO 2 The content of B 2 O 3 The ratio between the content of SiO 2 / B 2 O 3 Controlling it within the range of 0.4 to 4.0 is beneficial to improving the anti-crystallization property of the glass and optimizing the weather resistance and Young's modulus of the glass. 2 / B 2 O 3 0.4 to 4.0, more preferably SiO 2 / B 2 O 3 is 0.5 to 3.0, and SiO is more preferred 2 / B 2 O 3 0.6 to 2.0, more preferably SiO 2 / B 2 O 3 It is 0.7~1.2.

[0045] La 2 O 3It is an effective component for improving the refractive index of glass and has a significant effect on improving the chemical stability and resistance to devitrification of glass. If its content is less than 35%, it is difficult to achieve the required optical constants; if the content is higher than 50%, the devitrification tendency of the glass increases and the thermal stability deteriorates. Therefore, La 2 O 3 The content of is limited to 35-50%, preferably 37-47%, more preferably 41-46%.

[0046] G 2 O 3 It can increase the refractive index and chemical stability of glass and improve the thermal stability of glass. However, if its content is too high, the resistance to devitrification of glass will deteriorate and the cost of raw materials will increase. 2 O 3 The content of is 6 to 20%, preferably 8 to 18%, and more preferably 11 to 15%.

[0047] In some embodiments, SiO 2 and B 2 O 3 Total content of SiO 2 +B 2 O 3 With Gd 2 O 3 The ratio between the contents of SiO 2 +B 2 O 3 ) / Gd 2 O 3 Controlling it within the range of 0.3 to 2.5 can optimize the abrasiveness and bubble degree of the glass and increase the Young's modulus of the glass. 2 +B 2 O 3 ) / Gd 2 O 3 0.3 to 2.5, more preferably (SiO 2 +B 2 O 3 ) / Gd 2 O 3 is 0.4 to 2.0, more preferably (SiO 2 +B 2 O 3 ) / Gd 2 O 3 is 0.5 to 1.5, and more preferably (SiO 2 +B 2 O 3 ) / Gd 2 O 3 It is 0.7~1.2.

[0048] In some embodiments, B 2 O 3 and La 2 O 3 Total content B 2 O 3 +La 2 O 3 With Gd 2 O 3 and SiO 2 Total content of Gd 2 O 3 +SiO 2 The ratio between 2 O 3 +La 2 O 3 ) / (Gd 2 O 3 +SiO 2 ) is controlled within the range of 1.5 to 5.5, which is beneficial to reducing the density of the glass and improving the chemical stability of the glass. 2 O 3 +La 2 O 3 ) / (Gd 2 O 3 +SiO 2 ) is 1.5 to 5.5, more preferably (B 2 O 3 +La 2 O 3 ) / (Gd 2 O 3 +SiO 2 ) is 2.0 to 4.0. Further, control (B 2 O 3 +La 2 O 3 ) / (Gd 2 O 3 +SiO 2 ) is within the range of 2.3 to 3.3, the bubble degree and Young's modulus of the glass can be further optimized. 2 O 3 +La 2 O 3 ) / (Gd 2 O 3 +SiO 2 ) is 2.3 to 3.3, and more preferably (B 2 O 3 +La 2 O 3 ) / (Gd 2 O 3 +SiO2 ) is 2.5~3.2.

[0049] Y 2 O 3 It can improve the refractive index and devitrification resistance of glass. If its content is too high, the chemical stability and weather resistance of glass will deteriorate. 2 O 3 The content of is 0 to 6%, preferably 0 to 4%, and more preferably 0.1 to 3%.

[0050] In some embodiments, La 2 O 3 , Y 2 O 3 and Gd 2 O 3 Total content La 2 O 3 +Y 2 O 3 +Gd 2 O 3 When La is controlled within the range of 45-65%, the glass can more easily obtain the desired refractive index and Abbe number, and optimize the glass's resistance to devitrification and weather resistance. 2 O 3 +Y 2 O 3 +Gd 2 O 3 45 to 65%, more preferably La 2 O 3 +Y 2 O 3 +Gd 2 O 3 50 to 63%, more preferably La 2 O 3 +Y 2 O 3 +Gd 2 O 3 It is 52 to 60%.

[0051] Yb 2 O 3 It is a component that gives glass high refractive index and low dispersion properties. If its content exceeds 8%, the anti-crystallization performance of the glass will decrease. 2 O 3 The content of Yb is 0 to 8%, preferably 0 to 5%, more preferably 0 to 1%, and more preferably no Yb 2 O 3 .

[0052] ZrO 2It can improve the resistance to devitrification of glass, improve the chemical stability and mechanical properties of glass. If its content is too high, the melting difficulty of glass will increase, the melting temperature will rise, and inclusions will appear inside the glass and the light transmittance will decrease. 2 The content of is 3 to 13%, preferably 4 to 11%, and more preferably 6 to 10%.

[0053] In some embodiments, SiO 2 , B 2 O 3 and La 2 O 3 Total content of SiO 2 +B 2 O 3 +La 2 O 3 with ZrO 2 The ratio between the contents of SiO 2 +B 2 O 3 +La 2 O 3 ) / ZrO 2 Controlling it within the range of 4.0 to 15.0 can improve the Young's modulus and hardness of the glass and optimize the weather resistance of the glass. 2 +B 2 O 3 +La 2 O 3 ) / ZrO 2 4.0 to 15.0, more preferably (SiO 2 +B 2 O 3 +La 2 O 3 ) / ZrO 2 5.0 to 12.0, more preferably (SiO 2 +B 2 O 3 +La 2 O 3 ) / ZrO 2 6.5 to 10.0, more preferably (SiO 2 +B 2 O 3 +La 2 O 3 ) / ZrO 2 It is 7.5 to 9.0.

[0054] In some embodiments, B 2 O 3 The content of ZrO 2 and Y2 O 3 Total content of ZrO 2 +Y 2 O 3 The ratio B 2 O 3 / (ZrO 2 +Y 2 O 3 ) is controlled within the range of 0.2 to 2.5, which can improve the chemical stability and thermal expansion coefficient of the glass and prevent the hardness of the glass from decreasing. 2 O 3 / (ZrO 2 +Y 2 O 3 ) is 0.2 to 2.5, more preferably B 2 O 3 / (ZrO 2 +Y 2 O 3 ) is 0.4 to 2.0, and B is more preferably 2 O 3 / (ZrO 2 +Y 2 O 3 ) is 0.5 to 1.5, and B is more preferably 2 O 3 / (ZrO 2 +Y 2 O 3 ) is 0.6~1.0.

[0055] Nb 2 O 5 The refractive index and devitrification resistance of glass can be improved, and the thermal expansion coefficient of glass can be reduced. In the present invention, by containing 3% or more Nb 2 O 5 In order to obtain the above effects, Nb is preferably 2 O 5 The lower limit of the content of Nb is 5%, and the more preferred lower limit is 7%. 2 O 5 The content of Nb exceeds 15%, the thermal stability and weather resistance of the glass decrease, and the light transmittance decreases. Therefore, in the present invention, 2 O 5 The upper limit of the content is 15%, preferably 13%, and more preferably 12%.

[0056] In some embodiments, La 2 O 3 and Gd 2 O 3 Total content La 2 O 3 +Gd2 O 3 With Nb 2 O 5 The ratio between the contents of 2 O 3 +Gd 2 O 3 ) / Nb 2 O 5 Controlling it within the range of 3.5 to 15.0 is beneficial for the glass to obtain the desired refractive index and Abbe number while reducing the thermal expansion coefficient of the glass and optimizing the light transmittance and Young's modulus. 2 O 3 +Gd 2 O 3 ) / Nb 2 O 5 3.5 to 15.0, more preferably (La 2 O 3 +Gd 2 O 3 ) / Nb 2 O 5 is 4.0 to 10.0, and more preferably (La 2 O 3 +Gd 2 O 3 ) / Nb 2 O 5 is 5.0 to 8.0, and more preferably (La 2 O 3 +Gd 2 O 3 ) / Nb 2 O 5 It is 5.5 to 6.5.

[0057] TiO 2 It can increase the refractive index of glass, improve the stability of glass, and reduce the density of glass. If its content is too high, the Abbe number of glass will be difficult to meet the design requirements, and the light transmittance of glass will be reduced. 2 The content of is 8 to 22%, preferably 10 to 20%, and more preferably 13 to 18%.

[0058] In some embodiments, B 2 O 3 The content of TiO 2 The ratio of the content of 2 O 3 / TiO 2 Controlling it within the range of 0.1 to 1.0 can improve the bubble degree and chemical stability of the glass and prevent the light transmittance of the glass from decreasing. 2 O 3 / TiO 2 0.1 to 1.0, more preferably B 2 O 3 / TiO 2 is 0.2 to 0.8, and B is more preferred 2 O 3 / TiO 2 is 0.2 to 0.7, and B is more preferred 2 O 3 / TiO 2 It is 0.3~0.5.

[0059] In some embodiments, Gd 2 O 3 , Nb 2 O 5 and TiO 2 Total content of Gd 2 O 3 +Nb 2 O 5 +TiO 2 With SiO 2 and B 2 O 3 Total content of SiO 2 +B 2 O 3 The ratio between 2 O 3 +Nb 2 O 5 +TiO 2 ) / (SiO 2 +B 2 O 3 ) is controlled within the range of 1.0 to 8.0, which is beneficial to reducing the density and thermal expansion coefficient of the glass and improving the chemical stability and light transmittance of the glass. 2 O 3 +Nb 2 O 5 +TiO 2 ) / (SiO 2 +B 2 O 3 ) is 1.0 to 8.0, and more preferably (Gd 2 O 3 +Nb 2 O 5 +TiO 2 ) / (SiO 2 +B 2 O 3 ) is 1.5 to 6.0, and more preferably (Gd 2 O 3 +Nb 2 O5 +TiO 2 ) / (SiO 2 +B 2 O 3 ) is 2.0 to 5.0, and more preferably (Gd 2 O 3 +Nb 2 O 5 +TiO 2 ) / (SiO 2 +B 2 O 3 ) is 2.5~4.0.

[0060] In some embodiments, Gd 2 O 3 and TiO 2 Total content of Gd 2 O 3 +TiO 2 with La 2 O 3 and Nb 2 O 5 Total content La 2 O 3 +Nb 2 O 5 The ratio between 2 O 3 +TiO 2 ) / (La 2 O 3 +Nb 2 O 5 ) is controlled within the range of 0.3 to 0.9, which can optimize the density and abrasiveness of the glass and improve the anti-crystallization performance and weather resistance of the glass. 2 O 3 +TiO 2 ) / (La 2 O 3 +Nb 2 O 5 ) is 0.3 to 0.9, more preferably (Gd 2 O 3 +TiO 2 ) / (La 2 O 3 +Nb 2 O 5 ) is 0.35 to 0.8, and more preferably (Gd 2 O 3 +TiO 2 ) / (La 2 O 3 +Nb 2 O 5) is 0.4 to 0.7, and more preferably (Gd 2 O 3 +TiO 2 ) / (La 2 O 3 +Nb 2 O 5 ) is 0.45~0.6.

[0061] In some embodiments, B 2 O 3 and La 2 O 3 Total content B 2 O 3 +La 2 O 3 With Gd 2 O 3 , Nb 2 O 5 、TiO 2 Total content of Gd 2 O 3 +Nb 2 O 5 +TiO 2 The ratio between 2 O 3 +La 2 O 3 ) / (Gd 2 O 3 +Nb 2 O 5 +TiO 2 ) is controlled within the range of 0.7 to 2.5, which can improve the bubble degree of the glass and prevent the Young's modulus and hardness of the glass from deteriorating. 2 O 3 +La 2 O 3 ) / (Gd 2 O 3 +Nb 2 O 5 +TiO 2 ) is 0.7 to 2.5, more preferably (B 2 O 3 +La 2 O 3 ) / (Gd 2 O 3 +Nb 2 O 5 +TiO 2 ) is 0.8 to 2.0, and more preferably (B 2 O 3 +La 2 O 3) / (Gd 2 O 3 +Nb 2 O 5 +TiO 2 ) is 0.9 to 1.7, and more preferably (B 2 O 3 +La 2 O 3 ) / (Gd 2 O 3 +Nb 2 O 5 +TiO 2 ) is 1.0~1.5.

[0062] ZnO can improve the resistance of glass to devitrification, improve the solubility of glass raw materials, and reduce the high-temperature viscosity and transition temperature of glass. If the content of ZnO is too high, the difficulty of glass molding increases and the thermal stability deteriorates. Therefore, the content of ZnO is 0-5%, preferably 0-4%, and more preferably 0.1-3%.

[0063] In some embodiments, ZnO and Y 2 O 3 Total content of ZnO+Y 2 O 3 With Gd 2 O 3 The ratio between the contents of ZnO+Y 2 O 3 ) / Gd 2 O 3 Controlling below 0.8 is beneficial to improving the Young's modulus and anti-crystallization performance of the glass. 2 O 3 ) / Gd 2 O 3 is 0.8 or less, more preferably (ZnO+Y 2 O 3 ) / Gd 2 O 3 is less than 0.6. Further, control (ZnO+Y 2 O 3 ) / Gd 2 O 3 In the range of 0.01 to 0.5, the bubble degree of the glass can be further optimized. 2 O 3 ) / Gd 2 O 3 is 0.01 to 0.5, and more preferably (ZnO+Y 2 O 3 ) / Gd 2 O3 It is 0.05~0.3.

[0064] In some embodiments, the content of ZnO and SiO 2 and B 2 O 3 Total content of SiO 2 +B 2 O 3 The ratio between ZnO / (SiO 2 +B 2 O 3 ) is controlled below 0.8, which is beneficial to improving the chemical stability and bubble degree of the glass. Therefore, ZnO / (SiO 2 +B 2 O 3 ) is 0.8 or less, and more preferably ZnO / (SiO 2 +B 2 O 3 ) is less than 0.6. Further, the ZnO / (SiO 2 +B 2 O 3 ) is within the range of 0.01 to 0.5, the thermal expansion coefficient of the glass can be further optimized. Therefore, ZnO / (SiO 2 +B 2 O 3 ) is 0.01 to 0.5, and ZnO / (SiO 2 +B 2 O 3 ) is 0.02~0.3.

[0065] Alkaline earth metal oxide RO (RO is one or more of MgO, CaO, SrO, BaO) can adjust the optical constants of glass and optimize the chemical stability of glass, but when its content is high, the devitrification resistance of glass decreases. Therefore, the content of RO is limited to 0-6%, preferably 0-4%, and more preferably 0-2%. In some embodiments, it is further preferred that RO is not contained.

[0066] In some embodiments, the content of RO is related to Nb 2 O 5 The ratio between the content of RO / Nb 2 O 5 Controlling it below 0.8 is beneficial to reducing the thermal expansion coefficient of the glass and preventing the glass from losing its weather resistance and anti-crystallization properties. 2 O 5 0.8 or less, more preferably RO / Nb 2 O 5 is 0.5 or less, and more preferably RO / Nb2 O 5 0.3 or less, and more preferably RO / Nb 2 O 5 Is less than 0.1.

[0067] In some embodiments, B 2 O 3 ,La 2 O 3 , Y 2 O 3 Total content of B and RO 2 O 3 +La 2 O 3 +Y 2 O 3 +RO and Gd 2 O 3 The ratio between the contents of 2 O 3 +La 2 O 3 +Y 2 O 3 +RO) / Gd 2 O 3 Controlling it within the range of 2.0 to 7.0 can improve the weather resistance of the glass and optimize the abrasion resistance and thermal expansion coefficient of the glass. 2 O 3 +La 2 O 3 +Y 2 O 3 +RO) / Gd 2 O 3 2.0 to 7.0, more preferably (B 2 O 3 +La 2 O 3 +Y 2 O 3 +RO) / Gd 2 O 3 is 2.5 to 6.0, and more preferably (B 2 O 3 +La 2 O 3 +Y 2 O 3 +RO) / Gd 2 O 3 is 3.0 to 4.6, and more preferably (B 2 O 3 +La 2 O 3 +Y 2 O 3+RO) / Gd 2 O 3 It is 3.5 to 4.5.

[0068] Alkali metal oxide Rn 2 O(Rn 2 O is Li 2 O、Na 2 O.K 2 O) can reduce the transition temperature of glass, adjust the optical constants and high temperature viscosity of glass, and improve the melting property of glass. However, when its content is high, the devitrification resistance and chemical stability of glass are reduced. 2 The content of O is 0 to 5%, preferably 0 to 3%, and more preferably 0 to 1%. In some embodiments, it is further preferred that Rn 2 O.

[0069] WO 3 It can improve the refractive index and mechanical strength of glass. 3 If the content of WO exceeds 5%, the thermal stability of the glass decreases and the resistance to devitrification decreases. 3 The upper limit of the content of WO is 5%, preferably 3%, and more preferably 1%. In some embodiments, it is further preferred that WO 3 .

[0070] Ta 2 O 5 It has the effect of increasing the refractive index and improving the devitrification resistance of glass. However, if its content is too high, the thermal stability of the glass will decrease, the density will increase, and the optical constants will be difficult to control within the desired range. On the other hand, compared with other components, Ta 2 O 5 The price of Ta is very expensive, and from the perspective of practicality and cost, its usage should be reduced as much as possible. 2 O 5 The content of Ta is limited to 0-5%, preferably 0-3%, and more preferably 0-1%. In some embodiments, it is further preferred that Ta is not contained. 2 O 5 .

[0071] Al 2 O 3 It can improve the chemical stability of glass, but when its content exceeds 5%, the melting property and light transmittance of glass deteriorate. 2 O 3 The content of Al is 0-5%, preferably 0-3%, and more preferably 0-1%. In some embodiments, it is further preferred that Al is not contained. 2 O 3 .

[0072] P 2 O 5 It can improve the devitrification resistance of glass, but if its content is too high, the chemical stability will decrease. 2 O 5 The content of P is 0 to 4%, preferably 0 to 2%, more preferably 0 to 1%, and further preferably does not contain P 2 O 5 .

[0073] GeO 2 It has the effect of increasing the refractive index and resistance to devitrification, but if its content is too high, the chemical stability of the glass will decrease. On the other hand, compared with other components, GeO 2 The price of GeO is very expensive, and from the perspective of practicality and cost, its usage should be reduced as much as possible. 2 The content of GeO is limited to 0-3%, preferably 0-2%, more preferably 0-1%, and more preferably no GeO 2 .

[0074] In some embodiments, RO, GeO 2 , Y 2 O 3 and Ta 2 O 5 Total content of RO+GeO 2 +Y 2 O 3 +Ta 2 O 5 with La 2 O 3 The ratio between the contents of RO+GeO 2 +Y 2 O 3 +Ta 2 O 5 ) / La 2 O 3 Controlling it below 0.3 can optimize the bubble degree and abrasiveness of the glass and prevent the Young's modulus of the glass from deteriorating. Therefore, it is preferred that (RO+GeO 2 +Y 2 O 3 +Ta 2 O 5 ) / La 2 O 3 is 0.3 or less, more preferably (RO+GeO 2 +Y 2 O 3 +Ta 2 O 5 ) / La 2 O 3is 0.2 or less, and more preferably (RO+GeO 2 +Y 2 O 3 +Ta 2 O 5 ) / La 2 O 3 is 0.15 or less, and more preferably (RO+GeO 2 +Y 2 O 3 +Ta 2 O 5 ) / La 2 O 3 Is less than 0.1.

[0075] In the present invention, 0 to 1% Sb is contained 2 O 3 SnO 2 、CeO 2 One or more components in the glass can be used as a clarifier to improve the clarification effect of the glass and the bubble degree of the glass. The content of the clarifier is preferably 0 to 0.5%, and more preferably 0 to 0.2%. Since the component types and contents of the optical glass of the present invention are reasonably designed and the bubble degree is excellent, it is further preferred in some embodiments that no clarifier is contained. When Sb 2 O 3 When the content exceeds 1%, the glass tends to have a reduced clarity performance. At the same time, due to its strong oxidizing effect, it promotes the corrosion of platinum or platinum alloy vessels for melting glass and the deterioration of the molding mold. Therefore, Sb is preferably used in the present invention. 2 O 3 The content of Sb is 0 to 1%, more preferably 0 to 0.5%, further preferably 0 to 0.2%, and further preferably no Sb 2 O 3 SnO 2 It can also be used as a clarifier, but when its content exceeds 1%, the glass tends to be colored more, or when the glass is heated, softened, and molded again, Sn will become the starting point for the formation of crystal nuclei, resulting in a tendency to devitrification. 2 The content of SnO is preferably 0 to 1%, more preferably 0 to 0.5%, further preferably 0 to 0.2%, and further preferably does not contain SnO 2 . CeO 2 The role and content ratio of SnO 2 The content is preferably 0 to 1%, more preferably 0 to 0.5%, further preferably 0 to 0.2%, and further preferably CeO is not contained. 2 .

[0076] <Components that should not be contained>

[0077] In the glass of the present invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo are contained alone or in combination in small amounts, the glass will be colored and absorption will occur at specific wavelengths in the visible light region, thereby weakening the property of the present invention of improving the visible light transmittance. Therefore, it is preferably substantially free of oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, especially for optical glasses that require transmittance at wavelengths in the visible light region.

[0078] The oxides of Th, Cd, Tl, Os, Be and Se have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, it is preferred that they are not actually contained except for being inevitably mixed in. Thus, the optical glass does not actually contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present invention can be manufactured, processed and discarded.

[0079] In order to achieve environmental friendliness, the optical glass of the present invention preferably does not contain As 2 O 3 and PbO.

[0080] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing optical glass, there will be certain impurities or components that are not intentionally added, which will be contained in a small amount or trace amount in the final optical glass, and this situation is also within the scope of protection of the patent of this invention.

[0081] Next, the properties of the optical glass of the present invention will be described.

[0082] <Refractive Index and Abbe Number>

[0083] The refractive index of optical glass (n d ) and the Abbe number (ν d ) Tested according to the method specified in GB / T 7962.1-2010.

[0084] In some embodiments, the refractive index (n d ) has a lower limit of 1.98, a preferred lower limit of 1.99, a more preferred lower limit of 2.00, a further preferred lower limit of 2.01, and a further preferred lower limit of 2.03.

[0085] In some embodiments, the refractive index (n d ) is 2.15, preferably 2.10, and more preferably 2.07.

[0086] In some embodiments, the Abbe number (ν d ) has a lower limit of 22, a preferred lower limit of 23, a more preferred lower limit of 24, and a further preferred lower limit of 25.

[0087] In some embodiments, the Abbe number (ν d ) has an upper limit of 31, a preferred upper limit of 30, a more preferred upper limit of 29, and a further preferred upper limit of 28.

[0088] <Coefficient of Thermal Expansion>

[0089] Thermal expansion coefficient of optical glass (α -30 / 70℃ ) The data at -30~70℃ were tested according to the method specified in GB / T7962.16-2010.

[0090] In some embodiments, the thermal expansion coefficient (α -30 / 70℃ ) is 90×10 -7 / K or less, preferably 80×10 -7 / K or less, more preferably 75×10 -7 / K or less.

[0091] <Acid resistance stability>

[0092] Acid resistance stability of optical glass (D A ) (Powder method) Tested in accordance with the method specified in GB / T 17129.

[0093] In some embodiments, the acid resistance stability (D A ) is 2 or more types, preferably 1 type.

[0094] <Color>

[0095] The short-wave transmission spectrum characteristics of the glass of the present invention are expressed by the coloration (λ 70 and λ 5 ) indicates. 70 Refers to the wavelength when the glass transmittance reaches 70%. 70 The measurement is to use a glass with a thickness of 10±0.1mm and two opposite planes parallel to each other and optically polished, and measure the spectral transmittance in the wavelength range from 280nm to 700nm and the wavelength at which the transmittance is 70%. The so-called spectral transmittance or transmittance is the wavelength at which the incident intensity I is perpendicular to the above surface of the glass. in Light of intensity I passes through the glass and emerges from a plane out The light of the case through I out / I inThe amount expressed by λ also includes the transmittance of the surface reflection loss on the above surfaces of the glass. The higher the refractive index of the glass, the greater the surface reflection loss. Therefore, in high refractive index glass, λ 70 A small value of means that the glass itself is less colored and has a high light transmittance.

[0096] In some embodiments, the λ of the optical glass of the present invention is 70 480nm or less, preferably λ 70 470nm or less, preferably λ 70 Below 465nm.

[0097] In some embodiments, the λ of the optical glass of the present invention is 5 390nm or less, preferably λ 5 380nm or less, preferably λ 5 Below 375nm.

[0098] <Weather resistance>

[0099] The test method for weather resistance (CR) of optical glass is as follows: place the sample in a test box with a saturated water vapor environment of 90% relative humidity, alternately cycle every 1 hour at 40-50°C, and cycle for 15 cycles. The weather resistance category is divided according to the change in turbidity before and after the sample is placed. The weather resistance classification is shown in Table 1:

[0100] Table 1.

[0101]

[0102] In some embodiments, the weather resistance (CR) of the optical glass of the present invention is Class 2 or higher, preferably Class 1.

[0103] <Knoop hardness>

[0104] Knoop hardness of optical glass (H K ) The test shall be carried out according to the test method specified in GB / T7962.18-2010.

[0105] In some embodiments, the Knoop hardness (H K ) is 630×10 7 Pa or more, preferably 650×10 7 Pa or more, more preferably 660×10 7 Pa or above.

[0106] <Young's modulus>

[0107] Young's modulus (E) is calculated using the following formula by ultrasonic testing of its longitudinal wave velocity and transverse wave velocity.

[0108]

[0109] G=V S 2 ρ

[0110] Where: E is Young's modulus, Pa;

[0111] G is the shear modulus, Pa;

[0112] V T is the shear wave velocity, m / s;

[0113] V S is the longitudinal wave velocity, m / s;

[0114] ρ is the glass density, g / cm 3 .

[0115] In some embodiments, the Young's modulus (E) of the optical glass of the present invention is 11000×10 7 Pa or more, preferably 12000×10 7 Pa or more, more preferably 13000×10 7 Pa or above.

[0116] <Bubble Degree>

[0117] The bubble degree of optical glass is tested according to the method specified in GB / T7962.8-2010.

[0118] In some embodiments, the bubble degree of the optical glass of the present invention is above grade A, preferably grade A. 0 Grade A or above, preferably A 00 class.

[0119] <density>

[0120] The density (ρ) of optical glass is tested according to the method specified in GB / T7962.20-2010.

[0121] In some embodiments, the density (ρ) of the optical glass of the present invention is 5.50 g / cm 3 Below, preferably 5.40 g / cm 3 Below, more preferably 5.30g / cm 3 the following.

[0122] <Abrasion>

[0123] Abrasiveness of optical glass (F A ) refers to the value obtained by multiplying the ratio of the wear volume of the sample to the wear volume (volume) of the standard sample (H-K9 glass) under exactly the same conditions by 100, and is expressed by the following formula:

[0124] F A =V / V 0 ×100=(W / ρ) / (W 0 / ρ 0 )×100

[0125] Where: V—volume wear of the sample being tested;

[0126] V 0 —Volume loss of standard sample;

[0127] W—mass wear loss of the sample being tested;

[0128] W 0 —Abrasion loss of standard sample mass;

[0129] ρ—density of the sample being tested;

[0130] ρ 0 —Standard sample density.

[0131] In some embodiments, the abrasiveness (F A ) has a lower limit of 90, a preferred lower limit of 100, and a more preferred lower limit of 110.

[0132] In some embodiments, the abrasiveness (F A ) has an upper limit of 140, a preferred upper limit of 130, and a more preferred upper limit of 123.

[0133] [Method for producing optical glass]

[0134] The manufacturing method of the optical glass of the present invention is as follows: the glass of the present invention is produced using conventional raw materials and processes, including but not limited to using oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, etc.), boric acid, etc. as raw materials, and after the ingredients are prepared according to the conventional method, the prepared furnace materials are put into a melting furnace (such as platinum or platinum alloy crucible) at 1200-1450°C for melting, and after clarification and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.

[0135] [Glass preforms and optical components]

[0136] The prepared optical glass can be used to make a glass preform by means of direct drop molding, grinding, or compression molding such as hot press molding. That is, the molten optical glass can be directly precision drop molded into a glass precision preform, or the glass preform can be made by mechanical processing such as grinding and grinding, or the preform for compression molding made of the optical glass can be made by hot press molding and then grinding. It should be noted that the means for preparing the glass preform are not limited to the above means.

[0137] As described above, the optical glass of the present invention is useful for various optical elements and optical designs, and it is particularly preferred to form a preform from the optical glass of the present invention and use the preform to perform re-hot pressing, precision stamping, etc. to produce optical elements such as lenses and prisms.

[0138] The glass preform and optical element of the present invention are both formed of the optical glass of the present invention. The glass preform of the present invention has the excellent properties of optical glass; the optical element of the present invention has the excellent properties of optical glass, and can provide various optical elements such as lenses and prisms with high optical value.

[0139] Examples of the lens include various lenses having spherical or aspherical lens surfaces, such as a concave meniscus lens, a convex meniscus lens, a biconvex lens, a biconcave lens, a plano-convex lens, and a plano-concave lens.

[0140] [Optical instruments]

[0141] The optical element formed by the optical glass of the present invention can be used to manufacture optical instruments such as photographic equipment, video equipment, projection equipment, display equipment, vehicle-mounted equipment and monitoring equipment.

[0142] Example

[0143] <Optical Glass Example>

[0144] In order to further clearly illustrate and describe the technical solutions of the present invention, the following non-limiting examples are provided.

[0145] This embodiment adopts the above optical glass manufacturing method to obtain optical glasses having the compositions shown in Tables 2 to 4. In addition, the properties of each glass are measured by the testing method described in the present invention, and the measurement results are shown in Tables 2 to 4.

[0146] Table 2.

[0147]

[0148]

[0149]

[0150] Table 3.

[0151]

[0152]

[0153] Table 4.

[0154]

[0155]

[0156]

[0157] <Glass Preform Example>

[0158] The glass obtained from optical glass examples 1 to 24# is used, for example, by grinding processing, or by molding methods such as hot pressing, precision stamping, etc., to make preforms of various lenses, prisms, etc., such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses.

[0159] <Optical Element Embodiment>

[0160] The preforms obtained in the above-mentioned glass preform embodiments are annealed to reduce the internal stress of the glass and fine-tune the refractive index so that the optical properties such as the refractive index reach the desired values.

[0161] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.

[0162] <Optical Instrument Embodiment>

[0163] The optical element obtained by the above-mentioned optical element embodiment is optically designed to form an optical component or optical assembly by using one or more optical elements, and can be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, lithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips.

Claims

1. Optical glass, characterized in that: Its components, expressed in weight percentage, include: SiO2: 1-10%; B2O3: 1-10%; La2O3: 35-50%; Gd2O3: 6-20%; ZrO2: 3-13%; Nb2O5: 3-15%; TiO2: 8-22%, of which (B2O3+La2O3) / (Gd2O3+Nb2O5+TiO2) is 0.7-2.

5.

2. The optical glass according to claim 1, characterized in that: Its components are expressed in weight percentage and further contain: ZnO: 0-5%; and / or RO: 0-6%; and / or Rn2O: 0-5%; and / or WO3: 0-5%; and / or Ta2O5: 0-5%; and / or Al2O3: 0-5%; and / or Yb2O3: 0-8%; and / or GeO2: 0-3%; and / or P2O5: 0-4%; and / or clarifier: 0-1%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.

3. Optical glass, characterized in that: Its components, expressed in weight percentage, are SiO2: 1-10%; B2O3: 1-10%; La2O3: 35-50%; Gd2O3: 6-20%; ZrO2: 3-13%; Nb2O5: 3-15%; TiO2: 8-22%; ZnO: 0-5%; RO: 0~6%; Rn2O: 0~5%; WO3: 0~5%; Ta2O5: 0~5%; Al2O3: 0~5%; Yb2O3: 0~8%; GeO2: 0~3%; P2O5: 0~4%; Clarifier: 0-1% composition, wherein (B2O3+La2O3) / (Gd2O3+Nb2O5+TiO2) is 0.7-2.5, RO is one or more of MgO, CaO, SrO, BaO, Rn2O is one or more of Li2O, Na2O, K2O, and the clarifier is one or more of Sb2O3, SnO2, CeO2.

4. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage and meet one or more of the following 12 conditions: 1) SiO2+B2O3: 3-18%, preferably SiO2+B2O3: 5-15%, more preferably SiO2+B2O3: 7-13%; 2) La2O3+Y2O3+Gd2O3: 45-65%, preferably La2O3+Y2O3+Gd2O3: 50-63%, more preferably La2O3+Y2O3+Gd2O3: 52-60%; 3) (La2O3+Gd2O3) / Nb2O5 is 3.5 to 15.0, preferably (La2O3+Gd2O3) / Nb2O5 is 4.0 to 10.0, more preferably (La2O3+Gd2O3) / Nb2O5 is 5.0 to 8.0, and further preferably (La2O3+Gd2O3) / Nb2O5 is 5.5 to 6.5; 4) SiO2 / B2O3 is 0.4 to 4.0, preferably SiO2 / B2O3 is 0.5 to 3.0, more preferably SiO2 / B2O3 is 0.6 to 2.0, and further preferably SiO2 / B2O3 is 0.7 to 1.2; 5) (SiO2+B2O3) / Gd2O3 is 0.3-2.5, preferably (SiO2+B2O3) / Gd2O3 is 0.4-2.0, more preferably (SiO2+B2O3) / Gd2O3 is 0.5-1.5, and further preferably (SiO2+B2O3) / Gd2O3 is 0.7-1.2; 6) (SiO2+B2O3+La2O3) / ZrO2 is 4.0-15.0, preferably (SiO2+B2O3+La2O3) / ZrO2 is 5.0-12.0, more preferably (SiO2+B2O3+La2O3) / ZrO2 is 6.5-10.0, and further preferably (SiO2+B2O3+La2O3) / ZrO2 is 7.5-9.0; 7) B2O3 / TiO2 is 0.1 to 1.0, preferably B2O3 / TiO2 is 0.2 to 0.8, more preferably B2O3 / TiO2 is 0.2 to 0.7, and further preferably B2O3 / TiO2 is 0.3 to 0.5; 8) (Gd2O3+Nb2O5+TiO2) / (SiO2+B2O3) is 1.0 to 8.0, preferably (Gd2O3+Nb2O5+TiO2) / (SiO2+B2O3) is 1.5 to 6.0, more preferably (Gd2O3+Nb2O5+TiO2) / (SiO2+B2O3) is 2.0 to 5.0, and further preferably (Gd2O3+Nb2O5+TiO2) / (SiO2+B2O3) is 2.5 to 4.0; 9) (Gd2O3+TiO2) / (La2O3+Nb2O5) is 0.3-0.9, preferably (Gd2O3+TiO2) / (La2O3+Nb2O5) is 0.35-0.8, more preferably (Gd2O3+TiO2) / (La2O3+Nb2O5) is 0.4-0.7, and further preferably (Gd2O3+TiO2) / (La2O3+Nb2O5) is 0.45-0.6; 10) (B2O3+La2O3) / (Gd2O3+Nb2O5+TiO2) is 0.8 to 2.0, preferably (B2O3+La2O3) / (Gd2O3+Nb2O5+TiO2) is 0.9 to 1.7, and more preferably (B2O3+La2O3) / (Gd2O3+Nb2O5+TiO2) is 1.0 to 1.5; 11) (B2O3+La2O3) / (Gd2O3+SiO2) is 1.5 to 5.5, preferably (B2O3+La2O3) / (Gd2O3+SiO2) is 2.0 to 4.0, more preferably (B2O3+La2O3) / (Gd2O3+SiO2) is 2.3 to 3.3, and further preferably (B2O3+La2O3) / (Gd2O3+SiO2) is 2.5 to 3.2; 12) B2O3 / (ZrO2+Y2O3) is 0.2 to 2.5, preferably B2O3 / (ZrO2+Y2O3) is 0.4 to 2.0, more preferably B2O3 / (ZrO2+Y2O3) is 0.5 to 1.5, and further preferably B2O3 / (ZrO2+Y2O3) is 0.6 to 1.

0.

5. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage and meet one or more of the following five conditions: 1) (ZnO + Y2O3) / Gd2O3 is less than 0.8, preferably (ZnO + Y2O3) / Gd2O3 is less than 0.6, more preferably (ZnO + Y2O3) / Gd2O3 is 0.01 to 0.5, and further preferably (ZnO + Y2O3) / Gd2O3 is 0.05 to 0.3; 2) ZnO / (SiO2+B2O3) is 0.8 or less, preferably ZnO / (SiO2+B2O3) is 0.6 or less, more preferably ZnO / (SiO2+B2O3) is 0.01 to 0.5, and further preferably ZnO / (SiO2+B2O3) is 0.02 to 0.3; 3) RO / Nb2O5 is 0.8 or less, preferably RO / Nb2O5 is 0.5 or less, more preferably RO / Nb2O5 is 0.3 or less, and further preferably RO / Nb2O5 is 0.1 or less; 4) (B2O3+La2O3+Y2O3+RO) / Gd2O3 is 2.0 to 7.0, preferably (B2O3+La2O3+Y2O3+RO) / Gd2O3 is 2.5 to 6.0, more preferably (B2O3+La2O3+Y2O3+RO) / Gd2O3 is 3.0 to 4.6, and further preferably (B2O3+La2O3+Y2O3+RO) / Gd2O3 is 3.5 to 4.5; 5) (RO + GeO2 + Y2O3 + Ta2O5) / La2O3 is less than 0.3, preferably (RO + GeO2 + Y2O3 + Ta2O5) / La2O3 is less than 0.2, more preferably (RO + GeO2 + Y2O3 + Ta2O5) / La2O3 is less than 0.15, and further preferably (RO + GeO2 + Y2O3 + Ta2O5) / La2O3 is less than 0.1, The RO is one or more of MgO, CaO, SrO and BaO.

6. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: SiO2: 2-8%, preferably SiO2: 3-7%; and / or B2O3: 2-9%, preferably B2O3: 4-8%; and / or La2O3: 37-47%, preferably La2O3: 41-46%; and / or Y2O3: 0-4%, preferably Y2O3: 0.1-3%; and / or Gd2O3: 8-18%, preferably Gd2O3 : 11-15%; and / or ZrO2: 4-11%, preferably ZrO2: 6-10%; and / or Nb2O5: 5-13%, preferably Nb2O5: 7-12%; and / or TiO2: 10-20%, preferably TiO2: 13-18%; and / or ZnO: 0-4%, preferably ZnO: 0.1-3%; and / or RO: 0-4%, preferably RO: 0-2%; and / or Rn2O: 0-3%, preferably Rn2O: 0-1%; and / or WO3: 0-3%, preferably WO3: 0-1%; and / or Ta2O5: 0-3%, preferably Ta2O5: 0-1%; and / or Al2O3: 0-3%, preferably Al2O3: 0-1%; and / or Yb2O3: 0-5%, preferably Yb2O3: 0-1%; and / or GeO2: 0-2%, preferably GeO2: 0-1%; and / or P2O5: 0-2%, preferably P2O5: 0-1%; and / or clarifier: 0-0.5%, preferably clarifier: 0-0.2%, wherein RO is one or more of MgO, CaO, SrO, and BaO, Rn2O is one or more of Li2O, Na2O, and K2O, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.

7. The optical glass according to any one of claims 1 to 3, characterized in that: Its components do not contain WO3; and / or do not contain Ta2O5; and / or do not contain RO; and / or do not contain Rn2O; and / or do not contain P2O5; and / or do not contain Al2O3; and / or do not contain GeO2; and / or do not contain Yb2O3, and RO is one or more of MgO, CaO, SrO, and BaO, and Rn2O is one or more of Li2O, Na2O, and K2O.

8. The optical glass according to any one of claims 1 to 3, characterized in that: The refractive index n of the optical glass d is 1.98 to 2.15, preferably 1.99 to 2.10, more preferably 2.00 to 2.10, further preferably 2.01 to 2.10, and further preferably 2.03 to 2.

07. The Abbe number v d It is 22-31, preferably 23-30, more preferably 24-29, further preferably 25-28.

9. The optical glass according to any one of claims 1 to 3, characterized in that: The thermal expansion coefficient of the optical glass is α -30 / 70℃ 90×10 -7 / K or less, preferably 80×10 -7 / K or less, more preferably 75×10 -7 / K or less; and / or acid resistance stability D A Two or more types, preferably one type; and / or 70 480nm or less, preferably λ 70 470nm or less, preferably λ 70 is 465nm or less; and / or λ5 is 390nm or less, preferably λ5 is 380nm or less, more preferably λ5 is 375nm or less; and / or weather resistance CR is 2 or more, preferably 1; and / or Knoop hardness H K 630×10 7 Pa or more, preferably 650×10 7 Pa or more, more preferably 660×10 7 Pa or more; and / or Young's modulus E is 11000×10 7 Pa or more, preferably 12000×10 7 Pa or more, more preferably 13000×10 7 Pa or more; and / or the bubble degree is A grade or more, preferably A0 grade or more, more preferably A 00 Grade; and / or density ρ is 5.50g / cm 3 Below, preferably 5.40 g / cm 3 Below, more preferably 5.30g / cm 3 Below; and / or wear degree F A It is 90-140, preferably 100-130, more preferably 110-123.

10. A glass preform, characterized in that: Made of the optical glass described in any one of claims 1 to 9.

11. An optical element, characterized in that The optical glass is made of the optical glass described in any one of claims 1 to 9, or the glass preform described in claim 10.

12. An optical instrument, characterized in that Contains the optical glass according to any one of claims 1 to 9, and / or contains the optical element according to claim 11.